The Relationship between Sleep Pattern Disorders and Learning Concentration of Level 3 Nurse Students at STIKes Santa Elisabeth Medan - Pomarida Simbolon; Helinida Saragih; Era Jona Marantika Br. Barus (Jurnal EduHealth, 2023)
Concentration is one of the main factors that can affect the learning process, increasing one's concentration, the more effective learning activities are and vice versa, the factors that cause a person to have difficulty concentrating include thoughts, something will happen, lack of interest in lessons , crowded classroom conditions, unsupportive atmosphere, individual weakness in controlling his thoughts, and disturbed sleep patterns. The need for sleep will have an impact on a decrease in concentration, people who experience obstacles in the learning process caused by a sense of lack due to disturbing sleep patterns, so that their learning concentration decreases. The purpose of this study was to determine the relationship between sleep pattern disturbances and the learning concentration of Level 3 Nurses at STIKes Santa Elisabeth Medan 2022. This study uses a cross-sectional approach. This instrument uses a questionnaire. The number of samples in this study are 85 people. Analysis of the chi square test data with the results of the study. 12 out of 24 respondents (50.0%) had poor sleep pattern disorders with low learning concentration, 12 out of 24 respondents (50.0%) had sleep pattern disorders with high learning concentration, as many as 11 out of 61 respondents (18, 0% ) have a bad sleep pattern disorder with low learning concentration, 50 and 61 respondents (82.0%) have a good sleep pattern disorder with high learning concentration. Results Based on the chi square statistical test, a p-value of 0.Concentration is one of the main factors that can affect the learning process, increasing one's concentration, the more effective learning activities are and vice versa, the factors that cause a person to have difficulty concentrating include thoughts, something will happen, lack of interest in lessons , crowded classroom conditions, unsupportive atmosphere, individual weakness in controlling his thoughts, and disturbed sleep patterns. The need for sleep will have an impact on a decrease in concentration, people who experience obstacles in the learning process caused by a sense of lack due to disturbing sleep patterns, so that their learning concentration decreases. The purpose of this study was to determine the relationship between sleep pattern disturbances and the learning concentration of Level 3 Nurses at STIKes Santa Elisabeth Medan 2022. This study uses a cross-sectional approach. This instrument uses a questionnaire. The number of samples in this study are 85 people. Analysis of the chi square test data with the results of the study. 12 out of 24 respondents (50.0%) had poor sleep pattern disorders with low learning concentration, 12 out of 24 respondents (50.0%) had sleep pattern disorders with high learning concentration, as many as 11 out of 61 respondents (18, 0% ) have a bad sleep pattern disorder with low learning concentration, 50 and 61 respondents (82.0%) have a good sleep pattern disorder with high learning concentration. Results Based on the chi square statistical test, a p-value of 0.